The Role of Islamic Fintech in Sustainable Finance: Inclusion and Digitalization - Kamila, Niswa; Samsuri, Andriani (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2025)
Purpose: This study aims to analyze the effect of arm muscle training on improving chest pass skills in basketball, a fundamental technique essential for effective ball distribution between players. Methodology/Approach: A literature review method was employed by examining 18 scientific sources, including national and international journals and academic books published between 2004 and 2024. Thematic content analysis was used to identify the relationship between arm muscle training and chest pass proficiency. Results/Findings: The findings indicate that arm muscle training such as push-ups, weightlifting, and medicine ball chest pass drills significantly improve the power, accuracy, and distance of passes. These exercises also contribute positively to other basic basketball skills such as dribbling, shooting, and additional passing techniques. Statistical data from multiple studies confirm the effectiveness of such training on technical performance. Conclusions: Arm muscle training plays a vital role in enhancing chest pass effectiveness, particularly through the development of biceps and triceps strength. Therefore, this form of training should be integrated as a core component in structured basketball skill development programs. Limitations: This study is limited to a literature-based analysis without direct experimental validation, suggesting that further empirical research is needed to confirm the findings in real training environments. Contribution: The study offers a systematic and comprehensive synthesis of existing literature, which has not been extensively reviewed in this context, and provides practical guidance for coaches in designing targeted and evidence-based arm muscle training programs.